Application of 5G Internet System to Improve the Economy (Case Study of Bali Province) - Adi Kurniawan, Turkhamun; handayani, Popon; Pas Mahyu Akhirianto, Pas; Arman Syah Putra; Nurul Aisyah (International Journal of Science, Technology & Management, 2022)
The background of this research is to know the application of 5G in Denpasar Bali. With the application of 5G technology, what can be obtained to help in all fields, especially in the city of Denpasar Bali. The method used in this research is to use the literature review method, and implement the existing system on the 5G system in the city of Denpasar Bali. The problem raised in this research is how to find out the application of 5g technology that is needed by many people based on the problem of sending data or data supply because the data is too much and too large. It is known whether 5g technology can solve this problem so that it can help the community in making maximum use of data and sending data to help many things. The purpose of this research is how to find out the application of 5G technology in the city of Denpasar Bali, 5G technology that will be applied so that it can help many people, especially in terms of sending data and using virtual data because the data sent has started a lot and requires bigger technology. Again in sending data.